Peran Kemiskinan dan Inklusi Digital dalam Mewujudkan Pemerataan Akses Pendidikan di Indonesia - Septiana Handayani Sagala; Aryadimas Suprayitno (Yayasan Literasi Sains Indonesia, 2026)
The inequalities in the education sector in Indonesia that are the focus of this study include geographical, economic and education level aspects. In terms of infrastructure, only about 34% of schools in rural areas have adequate computer facilities. This study aims to investigate the effect of investment, poverty, economic conditions, and digitalization on education in Indonesia using panel data of 33 provinces during the period 2012-2021. The analysis technique used is static panel data regression with the Fixed Effect Model (FEM). The results showed that investment and digitalization variables were able to provide increased access to education equity. Conversely, an increase in poverty experienced by the community can reduce equality in education. Finally, national economic conditions have not been able to influence education equity. The findings of this study also detail the variation in the contribution of each province. The implementation of equal access to education in West Papua, Maluku and Aceh provinces does not depend on the four variables tested in this study. However, DKI Jakarta, Banten and West Java provinces are highly dependent on the four variables to improve equitable access to education. The results of this study contribute to policy recommendations for the Coordinating Ministry for Human Development and Culture of the Republic of Indonesia and local governments in creating equitable access to education.